What If My "I'm OK, You're OK" Is Different From Yours? Could the Inherent Optimism in Transactional Analysis Be a Form of Compulsory Ableism?. (2nd January 2021) - Oates, Steff
Abstract: The author challenges what she considers to be the potential oversimplification of the human condition in the way transactional analysis (TA) is sometimes taught. Referring to Steiner's idea of egalitarian empowerment available to all and taking inspiration from Robert McCruer's crip theory, she asks readers to question if the inherent optimism in TA is a version of compulsory ableism. She offers vignettes of reported experiences as well as some of her own in TA training and psychotherapy whereby clients and trainees felt marginalized for being differently abled. Using the title of Joyce McDougall's book, the author makes her own "plea for a measure of abnormality" and questions the application of some theoretical models (such as symbiosis) in their apparent pathologizing of those who have a vital need for others in order to provide a complementary function.